ИССЛЕДОВАНИЕ КОМПЛЕКСНОГО СОЕДИНЕНИЯ, ОБРАЗОВАННОГО 3-АМИНО-5-МЕРКАПТО-1,2,4-ТРИАЗОЛОМ С ЙОДИДОМ КАДМИЯ (II) (Scientific journal of the Fergana State University, 2026)
This article presents the methodology for synthesizing a new complex compound of 3-amino-5-mercapto-1,2,4-triazole with cadmium (II) iodide. The composition and structure of the complex were investigated using physicochemical methods. The synthesis conditions, crystalline structure of the complex, and its thermal stability were assessed using infrared (IR) spectroscopy, TG/DTA thermal analysis, and X-ray structural analysis. IR spectral analysis confirmed the presence of Cd-N and Cd-S coordination bonds. Thermal analysis revealed the stepwise decomposition of the compound, with CdO oxide identified as the final decomposition product. X-ray structural analysis showed that the complex belongs to the monoclinic crystal system (space group C2/c) with Cd2+ ions in sp3 hybridization surrounded by a tetrahedral geometry. The complex has a neutral polymeric structure, with one ligand coordinated in a monodentate manner and the other in a bidentate manner.